The politics of positionality: the difference between post-, anti-, and de-colonial methods. Issue 4 (1st October 2020) - Davis, Benjamin P.; Walsh, Jason
ABSTRACT: This essay works at the intersection of two trends, one longstanding and one relatively more recent. First, it takes place against the background of the overwhelming influence that the category of 'identity' exercises on both contemporary knowledge production and political practice. Second, it responds to what has been called the 'decolonial turn' in theory. We compare the work of Gayatri Spivak, Aijaz Ahmad, and Walter Mignolo in terms of the following question: What kind of reflexive method do they deploy in response to their recognition of the politics of knowledge production, that is, the existence of a relationship between social position and epistemic position? We then develop a novel distinction between post-colonial, anti-colonial, and de-colonial perspectives, one based not on backward-looking intellectual genealogies but on forward-looking political practices.